Ewolucja idei protekcjonizmu w teorii handlu międzynarodowego i praktyce współczesnej gospodarki światowej - Rynarzewski, Tomasz (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
Contemporary world economy is characterized by features which come off from foundations accepted in the classical and neoclassical theory of international trade. Models created within the framework of these theories cannot create a base for building analytic schema which allow to explain occurrences in present international division of labour. The purpose of this article is the attitude - on the basis of above remark - to relation between the idea of a free trade and protectionism. The author executes a synthetic review and an evaluation of so-called sockdolagers towards a usage of commercial barriers in a form of an educational tariff, an optimum tariff and a strategic trade policy. He adverts that they determine correct theoretically model constructions whose only practical difficulties of initiating underlie a present dominance of the free trade idea. He also underlines, that tendencies connected with a possible overcoming of pragmatic barriers in their wide usage can be dangerous for progressive development of future world economy. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1173, s. 308-319